Measuring and identifying large-study metrics for circadian rhythm disruption in female flight attendants - Grajewski, Barbara; Nguyen, Mimi M; Whelan, Elizabeth A; Cole, Roger J; Hein, Misty J (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'Flight attendants can experience circadian rhythm disruption due to travel through multiple time zones. The objectives of this study were to determine whether flight attendants are more likely than teachers (comparison group) to experience circadian disruption, as measured by melatonin production, and to identify metrics of circadian disruption for epidemiologic studies of reproductive health in which biomonitoring is infeasible. ' ' METHODS ': 'Each day, for one menstrual cycle, 45 flight attendants and 26 teachers kept a daily diary, collected and measured their overnight urine, and wore an activity monitor to assess sleep displacement. The relation between melatonin production and flight attendant and teacher status was analyzed with linear and multiple logistic regression. The relation between sleep displacement, melatonin, and flight-history-derived variables (including time zones crossed) were examined with exploratory factor analyses. ' ' RESULTS ': 'Flight attendants experience increased circadian disruption, as measured by a higher adjusted melatonin rate variance, than teachers [2.8 × 105 versus 1.0 × 105 (ng/hour)2, respectively; P=0.04] and are more likely to be in the highest quartile of melatonin variance (odds ratio 2.3; 95% confidence interval 0.6–9.1). In the factor analysis, the number of time zones crossed was related to both melatonin desynchronization and sleep displacement. ' ' CONCLUSIONS ': 'Flight attendants experience increased circadian disruption, as measured by more variable melatonin rates, than a minimally flying comparison group. For epidemiologic studies of flight crews in which melatonin measurement is infeasible, the number of time zones crossed is a useful indicator of both sleep displacement and melatonin desynchronization.
Keywords: aerospace medicine; circadian rhythm; circadian rhythm disruption; female; flight attendant; jet lag syndrome; large-study metrics; melatonin; sleep disorder; work schedule tolerance